2020
DOI: 10.31234/osf.io/dz9he
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relation of Teaching Quality to the Task Difficulty in Word Problems

Abstract: An important part of any math curriculum is solving word problems. Such problems are particularly difficult for many students. It has been shown that the difficulty of word problems arises from the characteristics of the problems themselves (e.g., arithmetic and linguistic characteristics) and the solver. However, very little is known about how the environmental factor teaching quality (i.e., cognitive activation, supportive climate and classroom management) influences successful solution of word problems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…However, all of the visual representations in these tasks were necessary or helpful for their solution. Previous research indicates that, in contrast, merely decorative illustrations do not affect performance in complex word problems (Lindner, 2020). Similarly, van Lieshout and Xenidou-Dervou (2018) showed that more demanding visual representations in prototype word problems affect solution rates than less demanding illustrations.…”
Section: Task Differencesmentioning
confidence: 94%
See 2 more Smart Citations
“…However, all of the visual representations in these tasks were necessary or helpful for their solution. Previous research indicates that, in contrast, merely decorative illustrations do not affect performance in complex word problems (Lindner, 2020). Similarly, van Lieshout and Xenidou-Dervou (2018) showed that more demanding visual representations in prototype word problems affect solution rates than less demanding illustrations.…”
Section: Task Differencesmentioning
confidence: 94%
“…Accordingly, Daroczy et al (2015) call for studies that differentiate at both the task level and the individual level to understand why particular students have difficulties with particular word problems. To our knowledge, the few studies that considered both the individual level and the task level usually focused on one or two specific aspects like verbal skills (Mullis et al, 2013;Pongsakdi et al, 2020;Vilenius-Tuohimaa et al, 2008), student background (Walkington et al, 2017), or environmental factors (Daroczy et al, 2020).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation